From Slave to Free. Apeleutheroi in the Sanctuary of Heracles at the Kynosarges in Athens - Valdés Guía, Miriam (ARYS. Antigüedad: Religiones y Sociedades, 2025)
In these pages we explore the role of freedmen and bastards in the sanctuary of Heracles, nothos par excellence, but also characterised as doulos, in the Kynosarges of Athens. We are exploring the possibility that this sanctuary was a place of manumission, and specifically, of the passage to the "complete liberation" of the apeleutheroi (thus becoming exeleutheroi) through private trials (dikai apostasiou), presided over by the polemarch. These processes would be particularly relevant in the context of the Peloponnesian War, a time of need for military troops, which would be reflected in Aristophanes' comedy of the Frogs. In it, Dionysus disguised as Herakles descends to Hades after consulting the hero in his sanctuary at Kynosarges, in a play that recalls the liberation of slaves in the Arginusas, and where changes of identity take place between Herakles and Dionysus and the slave and the master.
Keywords: Manumission; Herakles; Peloponnesian War; Exeleutheroi; Dike apostasiou